2016
DOI: 10.1111/add.13506
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette use in the European Union: analysis of a representative sample of 27 460 Europeans from 28 countries

Abstract: E-cigarette use in the European Union appears to be largely confined to current or former smokers, while current use and nicotine use by people who have never smoked is rare. More than one-third of current e-cigarette users polled reported smoking cessation and reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
125
1
9

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(142 citation statements)
references
References 45 publications
7
125
1
9
Order By: Relevance
“…The use of e-cigarettes is largely concentrated among adult smokers, most of whom report using e-cigarettes to quit smoking or for the purpose of smoking reduction. 2,3 However, substantial proportions of youth also report using e-cigarettes. In Canada, about 20% of youth aged 15-19 years report "ever trying" e-cigarettes, including 14% of youth nonsmokers, similar to estimates from the United Kingdom and the United States.…”
mentioning
confidence: 99%
“…The use of e-cigarettes is largely concentrated among adult smokers, most of whom report using e-cigarettes to quit smoking or for the purpose of smoking reduction. 2,3 However, substantial proportions of youth also report using e-cigarettes. In Canada, about 20% of youth aged 15-19 years report "ever trying" e-cigarettes, including 14% of youth nonsmokers, similar to estimates from the United Kingdom and the United States.…”
mentioning
confidence: 99%
“…E-cigarettes have been promoted as a safer alternative to tobacco products, with fewer adverse effects and as being efficient in smoking cessation. In this respect, a recent study conducted in 28 European countries suggested a positive public health impact for e-cigarette for the tobacco smokers accompanied by minimal potential harm due to use by never smokers [9]. However, this study based its findings on a little-harm model of e-cigarettes, which is not supported by scientific data.…”
Section: Introductionmentioning
confidence: 66%
“…We reported recently that the latest Eurobarometer survey data suggest there are more than 6 million ex-smokers in Europe who report that e-cigarettes helped them to quit smoking, and that current e-cigarette use is observed almost exclusively in smokers, which makes the 'gateway effect' unlikely [1]. The paper elicited two letters to which we wish to respond.…”
Section: E-cigarette Use In the European Union: Millions Of Smokers Cmentioning
confidence: 99%
“…Sir-We read with interest the paper written by Farsalinos and colleagues suggesting a role for e-cigarettes in smoking cessation and reduction among Europeans based on a cross-sectional survey [1]. They claim: 'Extrapolating to the whole European Union (EU) population, an estimated 6.1 million European have quit smoking with the use of e-cigarettes, while a further 9.1 million have reduced their smoking consumption' [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation